Benefits of animal-Assisted interventions in preschool children: A systematic review. (April 2023) - Lavín-Pérez, Ana Myriam; Rivera-Martín, Beatriz; Lobato-Rincón, Luis Lucio; Villafaina-Domínguez, Santos; Collado-Mateo, Daniel
Animal-assisted interventions are frequently used to stimulate and improve different skills in children with and without disabilities. However, the heterogeneity of AAI studies in preschool children is large, including different health conditions, duration, outcomes, study design or therapy animals. Therefore, the current study aims to summarize all intervention procedures and provide an updated analysis of the effectiveness of AAI intervention in the early childhood. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA), a systematic search was conducted in two databases: Pubmed (MedLine) and Web of Science. The risk of bias was assessed using the Evidence Project risk of bias tool. A total of 319 articles were identified and 17 were finally included in the qualitative synthesis. Due to the large heterogeneity in terms of study design, intervention, and sample characteristics, it was not possible to conduct a meta-analysis. Animal-assisted interventions might lead to a positive impact on physical, physiological, psychosocial, and language skills in preschool children. These enhancements may be observed both in healthy children and in those with different health conditions, such as intellectual disabilities, cerebral palsy, autism disorder, or Down syndrome. Results must be interpreted with caution due to the large heterogeneity and risk of bias in the included articles.